SAT0369 An audit of androgen deprivation therapy and bone protection in secondary care. (23rd January 2014) - Tiet, M.Y.; Abbas, A.; Whallett, A.
Abstract : Background: Prostate cancer is the most common cancer in men, with an incidence of 37, 000 in 2008 in the UK 1 . Androgen deprivation therapy plays an important role in prostate cancer treatment for many patients. However, hormone treatment is known to reduce bone density 2-3, even with short term use 4 . This may lead to morbidity from pathological fractures and has a negative correlation with survival 5 . Bisphosphonates and denosumab can be used to ameliorate these changes in bone mineralisation and thus reduce the incidence of fractures during use of anti-androgens 4, 6 . Currently there are no national guidelines regarding bone protection during and following use of androgen deprivation therapy. Objectives: To review whether clinicians are using risk stratification tools and investigations for androgen deprivation therapy related osteoporosis, with appropriate management implemented accordingly. Methods: We audited the management of bone protection in prostate cancer patients starting androgen deprivation therapy over a nineteen month period at Russells Hall Hospital, Dudley, West Midlands. Consideration for risk factors of osteoporosis by clinician use of risk stratification tools (FRAX®), dual-energy X ray absorptiometry (DEXA) scans and appropriate prescription of preventative treatment with calcium/vitamin D, bisphosphonates and denosumab were reviewed. Results: A total of 177 cases were analysed. During and following treatment FRAX® score had not been documented for any patient, even in cases of known osteoporosis, and only 2.8% had undergone a DEXA scan. Only 2.3% were prescribed calcium/vitamin D and 6.8% received bisphosphonates. Denosumab had not been prescribed throughout this period. Conclusions: Although osteoporosis is a risk with androgen deprivation therapy, here patients at risk of fracture had not been identified by lack of use of risk stratification tools and baseline DEXA scans. Yet delays in preventative treatment may have detrimental effects on skeletal health 7 . Agreed national guidelines and educating those managing prostate cancer care are required to make screening for at risk patients standard practice. Re-auditing following guidance is necessary. References: Office for National Statistics, 2010. Cancer Registrations in England 2008. Vahakn B, Shahinian, MD, Yong-Fang, K, Freeman J.L., and Goodwin JS. Risk of Fracture after Androgen Deprivation for Prostate Cancer. N Engl J Med 2005;352:154-164. Bruder JM, Ma JZ, Basler JW, Welch MD. Prevalence of osteopenia and osteoporosis by central and peripheral bone mineral density in men with prostate cancer during androgen-deprivation therapy. Urology 2006;67(1):152-5. Taxel P, Dowsett R, Richter L, Fall P, Klepinger A, Albertsen P. Risedronate prevents early bone loss and increased bone turnover in the first 6 months of luteinizing hormone-releasing hormone-agonist therapy for prostate cancer. J Urol 2002;168(3):1005-7. Oefelein MG, Ricchiuti V, Conrad W, Resnick MI. Skeletal fractures negatively correlate with overall survival in men with prostate cancer. J Urol 2002;168(3):1005-7. Greenspan SL. Approach to the prostate cancer patient with bone disease. J Clin Endocrinol Metab 2008;93:2-7. Greenspan SL, Nelson JB, Trump DL, Wagner JM, Miller ME, Perera S, and Resnick NM. Skeletal Health After Continuation, Withdrawal, or Delay of Alendronate in Men With Prostate Cancer Undergoing Androgen-Deprivation Therapy. J Clin Oncol 2008;20;26(27):4426-34. Disclosure of Interest: None Declared